KEDUDUKAN HUKUM POSITIF INDONESIA TERHADAP KEBIASAAN MASYARAKAT NELAYAN DALAM KEBIJAKAN BAGI HASIL PERIKANAN DI KECAMATAN MUNCAR KABUPATEN BANYUWANGI - Winarno, Djoko Wahju; Subekti, Rahayu; Candrakirana, Rosita (Yustisia, 2014)
The Act No. 16 year 1964 on Fisheries harvest-sharing regulated the policy of harvest-sharing on fisheries products in order to improve the welfare of the fishermen. However, the regulation seems to not running well, especially in Muncar District Banyuwangi Regency, where the fishermen were not familiar with the regulation and had their own customs on fisheries harvest-sharing which come across generations. This writing was applying the empirical legal study. The instruments were structured field interview towards fishermen, boat owner, and local government officials, which supported by literature review. Analysis was carried out by interactive model. This study found that the national regulation was unrecognized among the local fishermen and the harvest-sharing policy was based on their local customs. The harvest- sharing policy mostly was determined by the boat owner without former agreement. Therefore, the local government should supervise the application of the national regulation on harvest-sharing policy in order to improve the welfare status of the local fishermen. In addition, the ultimate social justice for the community will then be achieved.